2019
DOI: 10.4085/1062-6050-531-17
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Pain in People With Chronic Ankle Instability: A Systematic Review

Abstract: Objective To identify the prevalence of pain in people with chronic ankle instability (CAI) and how pain is related to the impairments of CAI. Data Sources We searched the databases of AMED, CINAHL, EMBASE, MEDLINE, PubMed, Scopus, SPORTDiscus, and Web of Science from inception to March 2017. Study Selection Eligible studies were peer-reviewed research in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 46 publications
0
27
0
6
Order By: Relevance
“…13 We selected the FADI for this investigation because of its emphasis on evaluating pain. In a recent systematic review, Al Adal et al 14 demonstrated that 50% to 79% of individuals with CAI reported ankle pain. Therefore, we selected a questionnaire that is used to evaluate this important symptom.…”
Section: Methodsmentioning
confidence: 99%
“…13 We selected the FADI for this investigation because of its emphasis on evaluating pain. In a recent systematic review, Al Adal et al 14 demonstrated that 50% to 79% of individuals with CAI reported ankle pain. Therefore, we selected a questionnaire that is used to evaluate this important symptom.…”
Section: Methodsmentioning
confidence: 99%
“…Since the measurement of IMI was only based on the medial malleolus, the rotation of the talus was not taken into account in this measurement. A positive value indicates the lateral malleolus was posterior to the 2 Journal of Orthopaedic Surgery 29 (1) plane of the medial malleolus. A negative value indicates the lateral malleolus was actually anterior to the plane of the medial malleolus.…”
Section: Mri Scan and Image Analysismentioning
confidence: 99%
“…In a recent systematic review, most studies reported that ankle pain was present in 50% to 79% of participants with chronic ankle instability. 7 Those pain was usually mild and intermittent and related to strenuous physical activity. 7 Surgical treatment is applied after comprehensive consideration of the degree of mechanical instability of the ankle joint evaluated by a surgeon and results of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Those pain was usually mild and intermittent and related to strenuous physical activity. 7 Surgical treatment is applied after comprehensive consideration of the degree of mechanical instability of the ankle joint evaluated by a surgeon and results of rehabilitation. Patients with ankle instability and chronic pain during walking or activity must be carefully screened for peroneal tendon injury, deltoid ligament or distal tibiofibular syndesmosis injury, osteochondral lesions, and traction injury of the nerves around the ankle joint, which are often accompanied by repetitive lateral ankle sprain (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation